2003
DOI: 10.4049/jimmunol.170.10.4986
|View full text |Cite
|
Sign up to set email alerts
|

Differential Control of Cell Cycle, Proliferation, and Survival of Primary T Lymphocytes by Purine and Pyrimidine Nucleotides

Abstract: Purine and pyrimidine nucleotides play critical roles in DNA and RNA synthesis as well as in membrane lipid biosynthesis and protein glycosylation. They are necessary for the development and survival of mature T lymphocytes. Activation of T lymphocytes is associated with an increase of purine and pyrimidine pools. However, the question of how purine vs pyrimidine nucleotides regulate proliferation, cell cycle, and survival of primary T lymphocytes following activation has not yet been specifically addressed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
167
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 210 publications
(176 citation statements)
references
References 46 publications
7
167
2
Order By: Relevance
“…5 and 6). Recently, we have demonstrated that purine and pyrimidine nucleotides play a critical role in the cell cycle progression, proliferation, and survival of human primary T lymphocytes in vitro (7,8). As T cell differentiation is closely linked to proliferation, we investigated to what extent inhibition of nucleotide synthesis could interfere with the acquisition of effector functions.…”
Section: Restriction Of De Novo Nucleotide Biosynthesis Interferes Wimentioning
confidence: 99%
See 2 more Smart Citations
“…5 and 6). Recently, we have demonstrated that purine and pyrimidine nucleotides play a critical role in the cell cycle progression, proliferation, and survival of human primary T lymphocytes in vitro (7,8). As T cell differentiation is closely linked to proliferation, we investigated to what extent inhibition of nucleotide synthesis could interfere with the acquisition of effector functions.…”
Section: Restriction Of De Novo Nucleotide Biosynthesis Interferes Wimentioning
confidence: 99%
“…This enzyme is strongly expressed in activated T and B cells (11). The antiproliferative effect of mycophenolate acid on T cells was clearly demonstrated in vitro (7,8,12,13). Methotrexate (MTX) is a folate antagonist that blocks dihydrofolate reductase and TS (14), but it can also block the first step of purine biosynthesis (15).…”
Section: Restriction Of De Novo Nucleotide Biosynthesis Interferes Wimentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is well described by the ability of 6-MP to prevent T cell proliferation, relevant in a severe inflammatory condition with rapid T cell expansion (8). This effect is observed at a relatively high dose of 6-MP (8), beyond clinically relevant dosages used chronically for IBD patients. In ∼50% of all patients with IBD, a low dose of azathioprine or 6-MP is given and well tolerated without major complications (9).…”
mentioning
confidence: 89%
“…Thereby, normal purine synthesis is hampered and incorporation of these alternative purines into newly synthesized DNA has long been the proposed therapeutic mechanism (7). This effect is well described by the ability of 6-MP to prevent T cell proliferation, relevant in a severe inflammatory condition with rapid T cell expansion (8). This effect is observed at a relatively high dose of 6-MP (8), beyond clinically relevant dosages used chronically for IBD patients.…”
mentioning
confidence: 89%